PRICE SETTING SYSTEM ON FINANCING OBJECTS IN BINTANG MANDIRI ACEH SHARIA COOPERATIVE IN THE CONTEXT OF MURÂBAHAH CONTRACT - Aditya Alhamdi; Jalaluddin (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
The murābahah contract's pricing is a crucial component of Islamic financial transactions, as it ensures the principles of transparency and equity. The objective of this investigation is to evaluate the application of the pricing system to financing at Bintang Mandiri Aceh Sharia Cooperative through an analysis of the murābahah contract. Qualitative research employs a descriptive-analytical methodology. Data were collected through direct observation, interviews with cooperative administrators, and a review of pertinent literature. The findings suggest that the selling price is established by incorporating a 16% annual profit margin into the cost of goods, while also considering operational costs, prospective financing risks, and the financial capacity of the members. Although this system is under Sharia principles, it is unable to provide cooperative members with comprehensive price information. It has been determined that the implementation of pricing principles that prioritize transparency and justice can enhance member satisfaction and welfare. This investigation proposes that cooperatives should enhance Sharia literacy among their management and strengthen their internal supervisory function to ensure the execution of the murābahah contract by Sharia provisions.